Prostaglandin E2 receptor 3 promotes M1 macrophages polarization in unexplained recurrent pregnancy loss. Issue 5 (3rd February 2022) - Ye, Yao; Peng, Lin; Chelariu-Raicu, Anca; Kuhn, Christina; Dong, Xi; Jeschke, Udo; von Schönfeldt, Viktoria
Abstract: Unexplained recurrent pregnancy loss (uRPL) is associated with macrophage polarization, which can be modulated by prostaglandin E2 (PGE2). Our previous study demonstrated that PGE2 receptor 3 (EP3) signaling is induced in the first-trimester placentas of uRPL patients compared with its expression in healthy controls. However, whether EP3 plays a role in macrophage polarization at the maternal-fetal interface of uRPL women remains unknown. The positive expression of EP3 in decidual macrophages was confirmed by double immunofluorescence staining in the first-trimester placentas collected from uRPL patients and healthy controls. Antibodies CD68, iNOS, and CD163 were used as immunofluorescence marker for decidual macrophages, M1, and M2 macrophages. To clarify the effects of EP3 on macrophage polarization, THP-1 monocyte cells were applied as M0 macrophages after phorbol 12-myristate 13-acetate (PMA) treatment for in vitro study. The mRNA levels of representative M1 markers (interleukin-1β and interleukin-6) and M2 markers (interleukin-10 and arginase-1) were quantified with qPCR in M0 macrophages being stimulated with sulprostone (an EP3 agonist) or L-798, 106 (an EP3 antagonist). We found that EP3 expression was upregulated in the decidual macrophages of first-trimester placentas from uRPL patients compared with healthy controls. Furthermore, EP3 expression was increased in M1 macrophages compared with that in M2 macrophages in first-trimester placentas of uRPL patients. Sulprostone intensified the mRNA levels of IL-6 together with interferon-γ, whereas L-798, 106 stimulated the mRNA expression of IL-10 and Arg-1 in a dose-dependent manner. Abstract : Increased expression of EP3 was associated with M1 macrophages polarization, which might influence the immunologic imbalance at the fetal-maternal interface in uRPL patients. Graphical Abstract: